Winners, Socially Displaced and Cinderellas: Representations of Race and Social Climbing in the Second Half of the Twentieth Century - Pietro Pisano (Universitas Humanística, 2014)
From the study of articles published in Colombian magazines (particularly Cromos magazine) in the second half of the twentieth century, this article proposes the analysis of some representations about upward mobility of black people. Consideration is given to the stories of some characters at different times: the judge Jose Antonio Camacho, the boxer Kid Pambelé, the model Laura Mosquera and the pianist Teresa Gómez. Although they emerged in different professional contexts, narratives about their paths have in common the emphasis on how the class representations articulated with the race and gender ones and were used to show the difficulty for a black person to be inserted in a social context different from the popular sectors, showing both their alleged incompatibility with the values of the middle class as well as the inability to fully integrate into a society dominated by whites.